Applicability of “ Platform Concept ” to machining function-integrated machine tools - A new “ Raison d'être ” for modular design - ITO, Yoshimi (Mechanical Engineering Reviews, 2015)
The current modular design has been established on the basis of engineering knowledge and concerns for the traditional machine tool, which has the limited machining function. With the growing importance of the machining function-integrated machine tool, we need to establish a new “ Raison d'être ” of the modular design, and a symptom is the “ Platform Concept ”. This paper reviews first the present perspective for the “ Platform Concept ” after quickly noting the modular design at present. The paper conceptualizes then a “ Platform-based Unit Construction ”, i.e., a variant of the new modular design, discusses its leading applications possible, and suggests a handful of research and engineering development subjects to establish it.